International opportunity recognition in Finnish property technology SMEs - Glader, Reetta (My University, 2023)
Globalization and the development of technology have speeded up internationalization of SMEs. While SMEs have directed their interest abroad, researchers have started to pay attention how international opportunity recognition precedes the actual internationalization. At the same time, rapid technological development has also enabled the growth of property technology (proptech) field over the past decades. Digital solutions aiming at reducing production and trading costs as well as improving efficiency and customer satisfaction are built around modern technologies, such as artificial intelligence, Internet of Things and blockchain. These solutions are utilized for various purposes in real estate, such as construction, maintenance, facility management, and financial services. Proptech field is increasingly internationalizing. In order to direct the scarce resources of SMEs to right places, it is important to the companies to understand how different factors influence their ability to recognize international opportunities. The purpose of this thesis is to understand what role do different factors on individual-, company-, network-, and environment-levels play in recognition of international opportunities in Finnish proptech SMEs. This study applies qualitative research methods. The empirical data was collected by interviewing central leading managers of four Finnish proptech SMEs. All interviewed companies have prior experience of international operations. The interviews were conducted virtually in spring 2020 during the COVID-19 pandemic. This study does not consider the possible impact of the pandemic to the subject, although it was ongoing during the time of the interviews. This study suggests that the recognition of international opportunities in proptech SMEs is directed by several factors on individual-, company-, network-, and environment-levels. On individual-level, the most important factors improving the recognition of international opportunities are international experience, technical knowledge, cross-cultural experience, and linguistic skills. On company-level, international experience helps companies to identify international opportunities easier and to evaluate the potentiality of opportunity and their own strengths more accurately. The more international experience from foreign markets companies have the more likely they are to systematically search for novel international opportunities than rely on experimental attempts. In addition, managers in central positions play a significant role in the decision considering internationalization. On network-level, companies are able to utilize various organizations that offer support for international opportunity recognition but are not willing to share their knowledge on internationalization with other companies. On environment-level, companies direct the recognition of international opportunities to countries with close geographic location and with similar culture and requirements for the quality of work to those in the domestic environment. Some international opportunities are also recognized through pure luck.

Globalisaatio ja teknologian kehitys ovat vauhdittaneet pienten ja keskisuurten yritysten kansainvälistymistä. Pk-yritysten suuntaaminen ulkomaan markkinoille on saanut tutkijat kiinnittämään huomiota itse kansainvälistymisen lisäksi siihen, miten yritykset tunnistavat kansainvälisiä mahdollisuuksia. Toisaalla, teknologian nopea kehitys on mahdollistanut kiinteistöteknologia-alan kasvun viime vuosikymmenien aikana. Nykypäivän teknologioiden, kuten tekoälyn, esineiden internetin ja lohkoketjun ympärille rakennetut sähköiset ratkaisut tuottavat tuotanto- ja kaupankäyntikuluja madaltavia sekä tehokkuutta ja asiakastyytyväisyyttä parantavia palveluita. Näitä palveluita hyödynnetään muun muassa rakentamisen, kiinteistönhuollon, työmaanjohdon ja taloushallinnon moninaisiin tarpeisiin. Koska kiinteistöteknologia-ala on kasvavassa määrin kansainvälistyvä, on yritysten kannalta tärkeää ymmärtää mitkä tekijät vaikuttavat niiden kykyyn tunnistaa kansainvälisiä mahdollisuuksia, jotta pk-yrityksen niukkoja resursseja osataan suunnata oikeisiin asioihin. Tämän pro gradu -tutkielman tarkoituksena on ymmärtää, miten eri tekijät yksilö-, yritys-, verkosto- ja ympäristötasoilla vaikuttavat siihen, miten suomalaiset kiinteistöteknologia-alan pk-yritykset tunnistavat kansainvälisiä mahdollisuuksia. Tutkimus on toteutettu laadullisena tutkimuksena haastattelemalla neljän suomalaisen kiinteistöteknologia-alan pk-yrityksen keskeisiä johtohenkilöitä. Kaikilla haastatelluilla yrityksillä on ollut aiempaa kokemusta kansainvälistymisestä. Haastattelut toteutettiin virtuaalisesti keväällä 2020, jolloin koronapandemia oli jo ehtinyt alkaa. Tutkimus ei kuitenkaan huomioi pandemian vaikutuksia aiheeseen. Tutkimuksen perusteella kiinteistöteknologia-alan yritysten kansainvälisten mahdollisuuksien tunnistamista ohjaa useat eri tekijät yksilö-, yritys-, verkosto- ja ympäristötasoilla. Yksilötason tärkeimmät mahdollisuuksien tunnistamista edistävät tekijät ovat kansainvälinen kokemus, tekninen osaaminen, kulttuurienvälinen kokemus ja kielitaito. Yritystasolla kansainvälisen kokemuksen todetaan auttavan yrityksiä tunnistamaan kansainvälisiä mahdollisuuksia nopeammin, sekä arvioimaan mahdollisuuksien potentiaalia ja omia vahvuuksiaan paremmin. Suurempi kansainvälinen kokemus myös ohjaa mahdollisuuksien tunnistamista systemaattiseen mahdollisuuksien etsintään. Lisäksi voidaan todeta, että yritystasolla keskeisillä johtohenkilöillä on suuri vaikutus kansainvälistymistä koskeviin päätöksiin. Verkostotasolla yritykset osaavat hyödyntää erilaisia tuki- ja katto-organisaatioita kansainvälisten mahdollisuuksien tunnistamisessa, mutta eivät ole valmiita jakamaan kansainvälistymistä koskevaa tietoa muiden yritysten kanssa. Ympäristötasolla yritykset suuntaavat kansainvälisten mahdollisuuksien tunnistamista mieluiten maihin, jotka ovat maantieteellisesti lähellä ja joissa on samanlainen kulttuuri ja työnteon laatuvaatimukset kuin kotimaassa. Osa kansainvälistymisen mahdollisuuksista tunnistetaan myös puhtaasti tuurilla.
Keywords: international opportunity recognition, internationalization, property technology, proptech, kansainvälisten mahdollisuuksien tunnistaminen, kansainvälistyminen, kiinteistöteknologia-ala